Damage assessment of fibre reinforced laminates - Durão, Luís Miguel P. (2015)
The use of solid wastes and natural fibres to the production of innovative composites is now a matter of environmental need. A set of hybrid composites constituted of waste rubber particles and sugarcane bagasse fibres into a thermoset composite material are drilled to determine the effect of rubber particle addition and size, sugarcane fibre addition and length and fibre chemical treatment on damage extension and related mechanical properties. Damage extension is determined by enhanced radiography for further damage measurement – diameter and areas – and correlated with mechanical test results — bearing test. The results demonstrated significant effect of the rubber and fibre additions on mechanical properties of the composites.